OPINI AUDIT GOING CONCERN INDUSTRI CONSUMER CYCLICAL: PERAN AUDIT TENURE DAN DEBT DEFAULT - Gracella Theotama; Agitiara Berliana Ranjani; Shirley Wijaya (E-Jurnal Akuntansi TSM, 2026)
This research aims to examine the influence of audit tenure and debt default on the issuance of going concern audit opinions. A quantitative approach was adopted for the secondary data samples. Previous studies have produced inconsistent findings. In this research, audit tenure is measured as the number of years since 2021, debt default is represented by the debt-to-equity ratio, and the going concern opinion is operationalized as a dummy variable. The company’s financial reports of 115 consumer cyclical corporations listed on IDX during the years 2021 to 2023 were analyzed. These companies were chosen through the application of purposive sampling. The results of the logistic regression test show that audit tenure negatively impacts going concern opinions. Conversely, debt default positively impacts going concern opinions.